Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia (SDM) terhadap Produktivitas (Usaha Mikro, Kecil dan Menengah (UMKM) (Studi pada UMKM Binaan Dindagkop dan UKM Kota Pekalongan) - Pratiwi Wulandari; Siti Nurhayati (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of training and human resource development on the productivity of Micro, Small and Medium Enterprises (MSMEs) assisted by Dindagkop and UKM Pekalongan City. Training and education is an activity carried out with the aim of improving and improving the quality of employees, which is carried out through increasing aspects of knowledge (knowledge) and operational skills (skills) in carrying out a job This research is quantitative research with data collection techniques using questionnaires, with the research subjects being 30 Micro, Small and Medium Enterprises (MSMEs) assisted by Dindagkop and UKM Pekalongan City who participated in HR training and development programmes. The data analysis technique used multiple linear regression analysis with the SPSS version 23 programme. The results of this study indicate that the Training Variable has a positive and significant effect on the MSME Productivity variable. Training variables have a positive and significant effect on MSME productivity variables. Training and HR Development variables simultaneously have a positive effect on the productivity of fostered MSMEs at Dindagkop and UKM Pekalongan City. Based on the recapitulation of questionnaire data, the indicator that obtained the largest average value was the frequency of old customers coming back and the indicator with the lowest average value was the increase in the number of customers. In addition, the results of the influence test of the Training (X1) and HR Development (X2) variables simultaneously affect MSME Productivity (Y) by 33.5%.